iRFP is a real time marker for transformation based assays in high content screening. - Viola Paulus-Hock; Eric C Cheung; Patricia Roxburgh; Karen H Vousden; Andreas K Hock (PLoS ONE)
Anchorage independent growth is one of the hallmarks of oncogenic transformation. Here we show that infrared fluorescent protein (iRFP) based assays allow accurate and unbiased determination of colony formation and anchorage independent growth over time. This protocol is particularly compatible with high throughput systems, in contrast to traditional methods which are often labor-intensive, subjective to bias and do not allow further analysis using the same cells. Transformation in a single layer soft agar assay could be documented as early as 2 to 3 days in a 96 well format, which can be easily combined with standard transfection, infection and compound screening setups to allow for high throughput screening to identify therapeutic targets.